Central Retinal Arterial Occlusion (CRAO) after Phacoemulsification-A Rare Complication - Lamichhane, Gyanendra; Gautam, P (Nepalese Journal of Ophthalmology, 2013)
Background: While peribulbar anesthesia is generally safe, a remote risk of retinal vascular accident exists and its routine use should be done with caution. Objective: To report a case of central retinal artery occlusion (CRAO) that occurred within 24 hours of routine uneventful phacoemulsification cataract surgery using peribulbar anesthesia. We share our experience of a 45-year old man who underwent uneventful clear corneal temporal incision phacoemulsification cataract surgery using peribulbar lignocain injection with adrenaline. Case: A Patient who underwent routine phacoemulsification surgery of left eye for posterior sub-capsular cataract under peribulbar anesthesia developed central retinal artery occlusion in the immediate post-operative period. The surgery was uneventful. Conclusion: Central retinal artery occlusion is a rare but dreadful complication seen after uneventful phacoemulsification and the cause is mainly due to anesthesia related. Nepal J Ophthalmol 2013; 5(10): 281-283 DOI: http://dx.doi.org/10.3126/nepjoph.v5i2.8746